Synthesis and characterization of new copolymers from glycidyl methacrylate and tetrahydrofurfuryl acrylate: determination of reactivity ratios - Azzahari, A.D.; Yahya, R.; Hassan, A.; Sheikh, M.R.K. (Springer Verlag, 2012)
The new copolymers from different feed compositions of glycidyl methacrylate (GMA) and tetrahydrofurfuryl acrylate (THFA) were synthesized using free radical polymerization in toluene at 70Â±1 Â°C using benzoyl peroxide (BPO) as initiator. The polymers were characterized by 1H NMR, 13C NMR and FTIR spectroscopic techniques. The polydispersities of the copolymers suggest a strong tendency for chain termination by disproportionation. The glass transition temperature of the copolymers increases with increase in GMA content. The thermal stability of the copolymers increases with increase in THFA content. The copolymer compositions were determined using 1H NMR analysis. Reactivity ratios for GMA and THFA as determined by the Mao-Huglin method were r 1=0. 379 and r 2=0. 266. The results showed that all these copolymerizations are strictly linear systems describable by the Mayo-Lewis equation based on the terminal model and that accurate reactivity ratio data can be obtained.